The Viscosity Effect of Masticated Natural vs. Synthetic Isoprene Rubber on Toughening of Polylactic Acid - Supanut Phattarateera; Cattaleeya Pattamaprom (International Journal of Polymer Science)
This study investigated the different viscosity effects of natural isoprene rubber (NR) compared to the synthetic one (IR) on toughening of polylactic acid (PLA). Here, 15 wt% rubber was melt blended with PLA in an internal mixer at 180°C and 50 rpm. It was found that the addition of these rubbers led to a significant increase in the tensile toughness and impact strength. These rubbers were masticated at 50°C and at 200 rpm for various mastication times to reduce their molecular weights. A too-long mastication time was found to adversely affect the impact strength and tensile toughness due to the fast agglomeration of rubber particles. At a comparable viscosity, it was remarkable that the impact strength of PLA/NR was higher than that of PLA/IR regardless of the similar chemical structures probably because the presence of nonrubber components including proteins and lipids could enhance the interfacial interaction between NR and the PLA matrix.